2013
DOI: 10.1007/s12094-013-1061-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular prognostic predictors of malignant peripheral nerve sheath tumor

Abstract: With this, the largest documented Chinese cohort, our data supply powerful Chinese evidence of the prognostic role of tumor size and NF1 status in MPNST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
86
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 26 publications
2
86
3
Order By: Relevance
“…Moreover, we found that a subtotal resection was associated with a higher risk of tumor recurrence. These data are in agreement with previous observations that the extent of resection affects the duration of PFS and OS 2,10,[19][20][21]42,52,56 and the risk of recurrence. 6,9,37,39,40,57 Considering the risk of recurrence in the present series, the variables that emerged as independent prognostic factors were a history of NF and a diagnosis of MPNST or PNNST.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, we found that a subtotal resection was associated with a higher risk of tumor recurrence. These data are in agreement with previous observations that the extent of resection affects the duration of PFS and OS 2,10,[19][20][21]42,52,56 and the risk of recurrence. 6,9,37,39,40,57 Considering the risk of recurrence in the present series, the variables that emerged as independent prognostic factors were a history of NF and a diagnosis of MPNST or PNNST.…”
Section: Discussionsupporting
confidence: 93%
“…In our opinion, the main strengths of this study are the long follow-up, the large number of patients/tumors, and the use of multivariate analysis (regression analysis). In fact, when looking at the literature (see Tables 2 and 3) we found only 3 studies with a duration of follow-up longer than in our series, 10,21,40 3 papers with a greater number of patients and wider tumors than our study, 2,14,35 and only a few articles analyzing surgical results and possible prognostic factors using a multivariate analysis. 2,5,20,21,30,31,42,57 The main limit of this study is the retrospective nature of the data, which could affect the results despite the strict statistical analysis.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…For individuals harboring a malignant peripheral nerve sheath tumor, despite adjuvant chemotherapy and radiation, the overall prognosis is poor, with 5-year disease-specific survival ranging between 35 and 50%. [2][3][4] In a large cohort, 41% of patients who initially presented with a localized malignant peripheral nerve sheath tumor developed distant metastasis in a median time of 12 months. 2 Cellular schwannoma initially described by Woodruff et al 5 is an uncommon, but wellrecognized, benign nerve sheath tumor that often presents diagnostic challenges.…”
mentioning
confidence: 99%